Prevalence of orbital floor reconstructon in zygomaticomaxilary complex fractures - Gani, Muhammad Sikander (My University, 2019)
Zygomaticomaxillary Complex (ZMC) fractures are a common phenomenon and tend to cause functional and aesthetic problems. Orbital wall involvement is commonly associated with ZMC fractures. There is a lack of consensus regarding the best surgical approach to these fractures. Many surgeons prefer a transcutaneous lower eyelid approach to the infraorbital rim approach with exploration of the internal orbit whereas others prefer to avoid it and use a transconjunctival approach to the internal orbit only if necessary. Avoiding the transcutaneous approaches and unnecessary exploration of the internal orbit results in fewer lower eyelid complications. The current trend is a minimally invasive approach to limit skin incisions and thus minimise external scars. This study aims to determine the prevalence of orbital wall reconstruction in ZMC fractures over a seven-year period (1 January 2010 to 31 December 2016) at the Charlotte Maxeke Johannesburg Academic Hospital. METHODS AND MATERIALS This study included 150 patients with isolated ZMC fractures at the Charlotte Maxeke Johannesburg Academic Hospital from 1 January 2010 to 31 December 2016. Isolated zygomatic arch fractures and multiple facial fractures that included the zygoma were excluded. Data on gender, age, aetiology, orbital fractures, and reconstruction, as well the surgical approaches and treatment were recorded. 4 RESULTS A total of 128 patients were male (85.31%) and 22 were female (14.67%) with a male to female ratio of 5.81:1. The ZMC fractures occurred mainly in the third decade (74 cases, 49.33%) of life with the left side being involved in 83 (55.37%) and the right side in 67 (44.67%) cases. Interpersonal violence (63%) was the main cause followed by road traffic accidents (34%). Orbital fractures were reported in 47 (31%) patients and orbital reconstruction was performed in 39(26%) patients. A statistical significance was noted with the infraorbital approach and orbital reconstruction. The majority of the patients (44%) had three surgical approaches (transoral maxillary vestibular, lateral brow, and infraorbital approaches) with 3-point fixation (46%). CONCLUSIONS Males comprised the majority of the patients in this study. The mean age was 31.5 years. A correlation between the infraorbital approach and orbital reconstruction showed that majority of the patients had transcutaneous approaches to the infraorbital rim even though orbital reconstruction was not required. This study shows that the international trends or protocols are not followed when treating ZMC fractures at this facility.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Dentistry to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg. June 2019.